2018
DOI: 10.15171/jarcm.2018.015
|View full text |Cite
|
Sign up to set email alerts
|

Negative appendectomy rate during 5 years in Modarres Hospital of Tehran, Iran, and correlation with imaging

Abstract: Appendicitis is the most common emergency surgical admission regardless of the age group. In case of delay in diagnosis, serious complications may occur, needing immediate actions. Complications of acute appendicitis like perforation, peritonitis, and sepsis are to justify massive negative appendectomies. In this study, it has been tried to collect data about negative appendectomy during last 5 years in Modarres hospital, Shahid Beheshti University of Medical sciences, Tehran, Iran, based on demographics and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
1
1
1
Order By: Relevance
“…In the same line, in a study conducted by Rashid-Azar et al (2017), suppurative appendicitis was the most common type that was observed on pathological examination (16). In a study performed by Nabipour in Kerman, Iran, and another research in Modarres Hospital, Tehran, Iran, 33.76% and 79.6% of cases were suffering from suppurative appendicitis, respectively, which were different from our findings in this study (5,15).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In the same line, in a study conducted by Rashid-Azar et al (2017), suppurative appendicitis was the most common type that was observed on pathological examination (16). In a study performed by Nabipour in Kerman, Iran, and another research in Modarres Hospital, Tehran, Iran, 33.76% and 79.6% of cases were suffering from suppurative appendicitis, respectively, which were different from our findings in this study (5,15).…”
Section: Discussioncontrasting
confidence: 99%
“…The early diagnosis of this disease is very important and challenging. In case of latency in diagnosis, serious complications, such as perforation, peritonitis, and sepsis may occur, which even might lead to death (3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%
“…24 In a study by Malekpour et al on all appendectomy cases during 5 years in a medical center in Tehran, fewer men than women had unnecessary appendix removal surgeries, which is in line with the present study. 41 In a study by Kadi et al, more appendectomies were performed in men and significantly, more women had unnecessary appendix surgeries, which confirms the results of the present study. 42 Other similar studies have emphasized the higher frequency of negative appendectomy cases in women than in men in all age groups.…”
Section: Discussionsupporting
confidence: 91%
“…Certain countries like Oman in central Asia have reported a negative appendectomy rate of 12.23%. In the East Asia the negative appendectomy rate is about 18.2% as reported in Hong Kong [10][11][12][13].…”
Section: Negative Appendectomy Defini-tion and Ratementioning
confidence: 99%